PENGARUH MODEL PEMBELAJARAN CROSSWORD PUZZLE PADA HASIL BELAJAR IPS SISWA KELAS V SD NEGERI TALANG LEBAN TAHUN AJARAN 2022/2023 - Utari Nurfitriana; Muhamad Idris; David Budi Irawan (STKIP Subang, 2023)
ABSTRACT This study aims to determine the effect of the crossword puzzle learning model on social studies learning outcomes for fifth grade elementary school students. The independent variable of this study is the crossword puzzle learning model and the dependent variable is student learning outcomes. The population in this study were 31 students in VA and VB classes. The sample in this study amounted to 31 people. The sampling technique was carried out by Simple random sampling. This experimental method uses a Quasy Experiment with a research design using a Nonequivalent Control Group Design. Documentation and test data collection techniques. The data analysis technique used in this study is the t-test. The results of the calculation of the data analysis data obtained the average value of the control class posttest results of 68.75 and 80.67 for the experimental class posttest. Based on the results of the t test analysis, the value of t_count = 2.255 is more than t_(table (0.05)) = 1.699 so that H_o is rejected, meaning H_a is accepted. So is the value of sig. Amounting to 0.032 <0.05. Thus there is an influence of the crossword puzzle learning model on student learning outcomes in Social Studies class V Elementary School. Keywords: Crossword Puzzle Learning Model, Student Learning Outcomes ABSTRAK Penelitian ini bertujuan untuk mengetahui pengaruh model pembelajaran crossword puzzle pada hasil belajar IPS siswa kelas V sekolah dasar. Variabel bebas dari penelitian ini yaitu model pembelajaran crossword puzzle dan variabel terikat yaitu hasil belajar siswa. Populasi dalam penelitian ini adalah siswa kelas VA dan VB yang berjumlah 31 orang. Sampel dalam penelitian ini berjumlah 31 orang. Teknik pengambilan sampel dilakukan dengan cara Simple random sampling. Metode eksperimen ini menggunakan Quasy Eksperiment dengan desain penelitian menggunakan Nonequivalent Control Group Design. Teknik pengumpulan data dokumentasi dan tes. Teknik analisis data yang digunakan dalam penelitian ini adalah uji-t. Hasil perhitungan data analisis data diperoleh nilai rata-rata hasil posttest kelas kontrol sebesar 68,75 dan 80,67 untuk posttest kelas eksperimen. Berdasarkan hasil analisis uji t menunjukkan nilai = 2,255 lebih dari = 1,699 sehingga ditolak berarti diterima. Begitu juga nilai sig. Sebesar 0,032 < 0,05. Dengan demikian terdapat pengaruh model pembelajaran crossword puzzle pada hasil belajar siswa pada mata pelajaran IPS kelas V Sekolah Dasar. Kata Kunci : Model Pembelajaran Crossword Puzzle, Hasil Belajar Siswa